ANALISIS PENGARUH PRODUK, PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN CUSTOMER D-LINK PADA PT. BERCA COMPUTEL. - KRIS DIPAYANTi (Inovasi, 2016)
ANALYSIS OF EFFECT OF PRODUCTS, PROMOTION AND PRICE ON PURCHASE DECISION D-LINK CUSTOMERS IN BERCA COMPUTEL. The purpose of this reserarch is to analize the influence of products, promotion and price of purchase at PT. Berca Computel. The independent variables are products (X1), promotion (X2) and price (X3) that influencing purchase decisions (Y) as the dependent variable. The sample, around 79 respondents, are Dlink product user customer.Based on research results, we obtained the regression  of equation: Y = 0.385 X1 + 0,165 X2 + 0,436 X3 . Testing result on hypothesis, indicates that the regression coefficient of the product with variable 0.385, followed by a promotion with a coefficient of regression and variable price with 0.165 koefiensi 0.436. Hypothesis testing using a t-test showed that the variables product, price and promotion proved to significantly affect the dependent variable purchase decisions. Figures adjusted R square of 0.941 or 94.1% indicates that purchasing decision variable can be explained by the variable of products, promotions and pricing. While the rest about 5.9% explained by other variables outside the variable of products, promotions and pricing that used in this study. Keyword : Product, Promotion, Price and Purcashing Decisions